PENGEMBANGAN MODEL EVALUASI KINERJA SDM BERBASIS BALANCED SCORECARD: STUDI PADA PERUSAHAAN JASA KONSULTAN - Nurfitriani, Nurfitriani; Kulsum, Umi; Sunarto, Sunarto; Heriyanto, Heriyanto (Jurnal GeoEkonomi, 2024)
This research aims to develop a Balanced Scorecard-based Human Resources (HR) performance evaluation model that suits the needs and characteristics of consulting services companies. Through a qualitative approach, data was collected through in-depth interviews, participant observation, and document analysis from five different consulting companies. The results of the analysis show that HR performance evaluation practices tend to be separated from the strategic planning process and are not aligned with the company's long-term goals. Based on these findings, a Balanced Scorecard-based HR performance evaluation model was developed, which includes financial, customer, internal process, and learning and growth dimensions. This model was then validated and field tested, which demonstrated its validity, relevance and implementability in the context of consulting services companies. The practical implication of this research is the importance of aligning performance evaluation with strategic planning to increase the effectiveness of HR performance management and support the achievement of consulting companies' business goals.